PENGARUH MOTIVASI KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. DROPSHIP GRAPHIC INDONESIA - Muhamad Ramadhan (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of work motivation and work environment on employee performance at PT. Dropship Graphic Indonesia either partially or simultaneously. The research used uses a quantitative approach. The sample used in the research was 75 respondents using Slovin. The data collection methods used were observation and questionnaires. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis, and hypothesis testing. The research results show that work motivation and work environment have a positive effect on employee performance both partially and simultaneouslys.